A Predominant Narration: A Comparative Study of The Solitude Experience of Exile in Shakespeare’s King Lear (1605) and Manto’s Toba Tek Singh (1955) - Binth e Zia, Atifa; Aamir, Khadija (Journal of Research in Humanities, 2023)
William Shakespeare’s King Lear (1605) is known for its projection of madness, similar to Toba Tek Singh (1955) penned by Sadat Hassan Manto. The paper aims to analyze the driving force behind this madness of characters of these two narratives. Both Shakespeare and Manto have presented it through the madness of characters and space, making exile a universal ideology. Thus, this study aims to research the concept of madness through journey via Edward W. Said’s Exile – “as a discontinuous state of being” (139). The exile of Cordelia and King Lear from Shakespeare’s play, King Lear will be demonstrated with a comparative study with the expatriate of Bishan Singh and other lunatics from Manto’s Toba Tek Singh. The research focuses on “the compound misery of “undocumented” people” who are banished just because of their deviance displayed in King Lear and Toba Tek Singh (Said 141).